Volcanic Landforms and Landscapes of the East Carpathians (Romania) and Their Geoheritage Values - Alexandru Szakács; Marinel Kovacs (Land, 2022)
The Neogene–Quaternary volcanic range running along the East Carpathians in Romania, extends from the Oaș Mountains, in the north-west, to the South Harghita Mountains and the Perșani Mountains, in the south-east, as part of the broader volcanic province of the Carpathian–Pannonian Region. It resulted from intense volcanic activity during the 15–0.1 Ma time interval, generating huge volumes of effusive and explosive products and a variety of volcanic edifices and primary landforms from large composite volcanoes to small-sized domes/dome-coulées/lava flows and volcaniclastic plateaus around them. The present-day landforms were shaped by various syn-volcanic deformation processes (such as volcano spreading), post-volcanic erosion of various degrees and types (including glacial erosion on the highest-elevation parts and relief inversion in the peripheral areas) and modern anthropic intervention. Developed on this diverse volcanic substrate, the present-day landscape shows a large variety of aspects due to further factors (original topography, elevation, vegetation cover, distance from settlements, anthropic activities, and degradation processes). This volcanic range hosts many geoheritage-relevant sites of various spatial extent (from hundreds of km2 to limited areas of a few 10 m2) and of protection status (from national parks, natural or scientific reserves, natural monuments, and protected areas to areas with no protection at all). Despite its high geoheritage potential, geoparks are still absent, geotrails are sparse, and geotourism is in its infancy in the East Carpathian volcanic range.